P16 Using in-situ simulation to improve the cross-specialty response to paediatric airway emergencies in a district general hospital. (3rd November 2019) - Farrands, Rebecca; Jacques, Andrew
Abstract : Background: Acute airway compromise is a leading cause of paediatric cardiopulmonary arrest. 1 Working in a District General Hospital (DGH) however, critical paediatric airway emergencies remain rare. It is essential that teams remain primed to respond rapidly when the need arises. Effective cross-speciality communication and access to familiar equipment are essential to prevent potentially devastating delays. Simulation is becoming an increasingly important tool to interrogating current practice, identifying problems and implementing change before patient harm occurs. 2 Summary of work: We ran an in-situ simulation using a high fidelity paediatric model to test our departmental response to a paediatric airway emergency involving multiple clinical teams. Run in real time, we recorded: the sequence of events; timings of key interventions and inter-team communication; and any equipment issues which arose. Summary of results: We demonstrated a number of avoidable delays which could significantly impact patient safety. The at-risk airway was recognised at just 5 minutes however it was 46 minutes until advanced paediatric airway support arrived. A further 14 minute delay occurred following anaesthetic induction, before the airway was secured, as appropriate paediatric advanced ENT airway equipment was not available in the emergency theatre. Discussion and conclusion: The absence of a clear pathway for escalation of paediatric airway concerns caused significant delays. Responders were uncertain who they should contact to rapidly access appropriate help. The greatest risk to impending airway obstruction however was the lack of appropriate ENT equipment in theatre following anaesthetic induction. Recommendations: Working directly with the on-call ENT team we have developed a clear pathway and identifiable trolley to include both anaesthetic and ENT emergency paediatric airway equipment. This universal (Make Airways Safe) MAST trolley is now standardised in ED and emergency theatres, minimising delays in that could potentially jeopardise the care of the critically ill child. We are replicating the MAST trolley in neighbouring DGHs covered by the same ENT on-call team. Our aim is to generate a standardised regional equipment trolley, increasing patient safety in time-critical airway emergencies. References: Kuisma M, Suominen P, Korpela R. Paediatric out-of-hospital cardiac arrests-epidemiology and outcome. Resuscitation . 1995 October;30(2):141–50. Davison M, Kinnear FB, Fulbrook P. Evaluation of a multiple-encounter in situ simulation for orientation of staff to a new paediatric emergency service: a single-group pretest/post-test study. BMJ Simul Technol Enhanc Learn 2017 October;3(4):149–153.